The infuence of content marketing and social media influencers on purchase decisions through consumer trust as an intervening in fresh milk products in Boyolali City - Zahra Dwi Maudina; Edy Purwo Saputro (Institute of Computer Science (IOCS), 2026)
This research examines how content marketing and social media influencers impact purchase decisions, using consumer trust as an intervening variable. The study focuses on fresh milk consumers in Boyolali City. Because previous studies show conflicting results regarding how digital marketing affects consumer behavior through trust, this study aims to fill that research gap. Using a quantitative causal design, primary data were collected from 121 fresh milk consumers via purposive sampling and structured questionnaires. Data analysis using SmartPLS 3.2 indicates that content marketing significantly and positively influences both consumer trust (?> 0; p < 0.05) and purchase decisions (? > 0; p < 0.05). While social media influencers significantly boost trust (? > 0; p < 0.0), they lack a statistically significant direct effect on buying behavior (p > 0.05). Furthermore, consumer trust positively impacts purchase decisions (?> 0; p < 0.05) and functions as a critical mediating variable that reinforces the overall relationship between marketing strategies and consumer actions. These findings highlight that trust is essential for turning digital marketing efforts into actual sales within the fresh milk industry.